The yeast nascent polypeptide-associated complex initiates protein targeting to mitochondria in vivo - George, Rebecca (The National Academy of Sciences, 1998)
The yeast nascent polypeptide-associated complex (NAC) is encoded by two genes, EGD1 and EGD2, and is associated with cytoplasmic ribosomes. Yeast mutants lacking NAC (Δegd2) are viable but suffer slight defects in the targeting of nascent polypeptides to several locations including the endoplasmic reticulum and mitochondria. If both NAC and Mft52p are missing from yeast cells, inefficient targeting of mitochondrial precursor proteins leads to defects in both mitochondrial function and morphology. We suggest that NAC provides a ribosomal environment for nascent mitochondrial targeting sequences to achieve secondary structure, thereby enhancing the efficiency of protein targeting.